PERKEMBANGAN HUKUM SEKTOR JASA KEUANGAN DALAM UPAYA PERCEPATAN PERTUMBUHAN EKONOMI NASIONAL - Tri Handayani; Lastuti Abubakar (Universitas Muhammadiyah Sumatera Utara, 2017)
Indonesia’s financial services sector shows a rapid development in line with changes in the regional and global sector. Taking a role in promoting the acceleration of national economic growth, financial services sector is directed to optimally play a role in stability of the financial system as a foundation for sustainable development, and realizing the financial independence of the community and supporting efforts to increase equity in Development (inclusive). This research uses normative juridical approach with analytical descriptive research specification. Data were analyzed by qualitative juridical. Based on the results of the research, the regulation in the financial services sector is growing rapidly as a result of regional and global demands, especially facing the ASEAN Banking Integration Framework (ABIF). Legal developments in the financial services sector are reflected in regulatory changes on institutional, service and product aspects as well as dispute resolution. There is still a need for legal reform that can provide a solid legal basis for the financial services sector, namely civil law reform and banking law.